Improving Timely Medication Access for Endocrinology and Diabetes Patients: A Quality Improvement Initiative - Wadah Almansoori; Hadeel Almasarweh; Ghassan Mohamadsalih; Khalid Hussain; Amal Aburamadan; Awais Tariq; Khaled Al-Surimi (Global Journal on Quality and Safety in Healthcare)
Introduction Managing chronic conditions such as endocrinology and diabetes requires consistent access to medications. Traditional methods of medication refill often involve in-person visits to healthcare providers or pharmacies, posing challenges for patients. Online medication refill services offer a promising solution to improve accessibility and convenience. Methods This is a digital-based solution using online medication refill services to enhance the management of endocrinology and diabetes medication refills. It examines the process of online medication refill, including patient registration, refill request submission, verification, provider input, processing, and pickup or delivery. Results Online medication refill services empower patients to easily request refills from the comfort of their homes, streamlining the refill process, and reducing walk-in pressure in clinics. The online medication refill with the option for home delivery option eliminates the need for patients to visit the hospital, further enhancing the patient experience. Before implementing the online medication refill solution, 26 patients will come to the clinic as walk-ins to request medication refills. The average waiting time for each patient is 45 minutes. Each provider will be interrupted for an average of 10 minutes to accommodate the request. The overall processing time required for each walk-in patient to submit the medication request is 1 hour on average. After implementing the online medication refill intervention, zero patients come to the clinic as walk-ins and hence, no interruption to the daily regular clinics. The overall processing time required for submitting the online medication request is now 2 minutes. These interventions promote medication adherence and patient engagement by facilitating access to medications and offering educational resources. Conclusion Online medication refill services represent a valuable tool in the comprehensive management of endocrinology and diabetes. They offer accessibility, convenience, and patient empowerment, potentially improving health outcomes and enhancing the overall patient experience.